2010
DOI: 10.1097/qad.0b013e3283377973
|View full text |Cite
|
Sign up to set email alerts
|

The association between cervical human papillomavirus infection and HIV acquisition among women in Zimbabwe

Abstract: Background The prevalence of HPV is higher among HIV+ women, but the prevalence of HPV prior to HIV acquisition has not been carefully evaluated. Objective This study evaluated whether HPV infection is independently associated with heterosexual HIV acquisition in a cohort of Zimbabwean women. Design Case-control study nested within a large multi-center cohort study (HC-HIV). Methods Cases consisted of Zimbabwean women with incident HIV infection observed during follow-up (n=145). HIV-uninfected controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 26 publications
12
103
0
2
Order By: Relevance
“…Therefore, the observed association between persistent HR HPV and new HSV-2 infection warrant further studies and should be interpreted with caution. However, several studies have found that HPV infection increases the risk for HIV acquisition by 1.8 -3.5 times [32]- [34]. Lissouba et al (2013) in their meta-analysis review found that HR HPV infection was associated with almost a 2-fold increased risk for incident HIV infection, while LR HPV infection had only a borderline association [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed association between persistent HR HPV and new HSV-2 infection warrant further studies and should be interpreted with caution. However, several studies have found that HPV infection increases the risk for HIV acquisition by 1.8 -3.5 times [32]- [34]. Lissouba et al (2013) in their meta-analysis review found that HR HPV infection was associated with almost a 2-fold increased risk for incident HIV infection, while LR HPV infection had only a borderline association [35].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Concordance of biological and behavioral risks was tested by the weighted kappa statistic. 16,17 This study was approved by the institutional ethics committee and followed the Guiding Medical Doctor recommendations of the Biomedical Research Involving Human Subjects and the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12] Clinical conditions like vulvovaginal ulcers, excoriations, cracks, cervicitis, or coinfections (Chlamydia trachomatis, herpes simplex, human papilloma virus -HPV) can all increase the risk of STD/AIDS. [8][9][10][11] Inflammatory nonulcerative genital conditions such as vulvovaginitis, cervicitis and pelvic inflammatory disease have also been shown to be important risk factors. Another consideration is that diagnosis of a sexually transmitted infection should increase suspicion of other STDs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations